Handbook of peer interactions, relationships, and groups - Bukowski, William M., 1954-; Laursen, Brett Paul; Rubin, Kenneth H. (The Guilford Press, 2018)
"The chapters in this book cover topics such as aggression, withdrawal, victimization, and psychopathology. Other chapters refer to broad forms of peer experience or types of relationships including friendships, romantic relationships, experiences in groups, and the intersection between peers and the family or to methods such as sociometry and behavior genetics that are used to study peer relations. Also discussed are the intrapersonal or interpersonal dynamics that regulate peer relations such as interpersonal conflict and the processes of moral judgment that affect intergroup relations as well as the developmental dynamics that affect the origins of peer relations in early childhood. Also described are variations in peer relations that are related to gender, culture, and race or that are due to environmental factors such as the school context"--Resumé vydavatele